2017
DOI: 10.1186/s13014-017-0784-1
|View full text |Cite
|
Sign up to set email alerts
|

An integrated strategy of biological and physical constraints in biological optimization for cervical carcinoma

Abstract: BackgroundFor cervical carcinoma cases, this study aimed to evaluate the quality of intensity-modulated radiation therapy (IMRT) plans optimized by biological constraints. Furthermore, a new integrated strategy in biological planning module was proposed and verified.MethodsTwenty patients of advanced stage cervical carcinoma were enrolled in this study. For each patient, dose volume optimization (DVO), biological model optimization (BMO) and integrated strategy optimization (ISO) plans were created using same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…On Eclipse, but using the specific biological optimization module based in TCP and NTCP (both Lyman and serial models), Kan reported that for nasopharyngeal cancer IMRT planning, the biological optimization yielded comparable TCP, relative to physical optimization, while presenting more hot spots in the target, better NTCP for parotids, no significant difference for serial organs. Similar conclusions were outlined by Feng for cervical cancer planning using IMRT and the same biological optimization module in Eclipse.…”
Section: Discussionsupporting
confidence: 77%
“…On Eclipse, but using the specific biological optimization module based in TCP and NTCP (both Lyman and serial models), Kan reported that for nasopharyngeal cancer IMRT planning, the biological optimization yielded comparable TCP, relative to physical optimization, while presenting more hot spots in the target, better NTCP for parotids, no significant difference for serial organs. Similar conclusions were outlined by Feng for cervical cancer planning using IMRT and the same biological optimization module in Eclipse.…”
Section: Discussionsupporting
confidence: 77%
“…Recurrence of HCC was observed in 3 patients. In the subset of 73 patients with primary liver tumors, toxicities included grade 2 ascites (1 patient), grade 3 ascites (1 patient), and grade 3 duodenal bleeding (1 patient) 7 months after completing treatment (22).…”
Section: Phase II Trialsmentioning
confidence: 99%
“…In addition, adding biological factors into the optimization stage of treatment plans can allow doctors to understand the prognostic effect of patients intuitively. There have been some studies (41)(42)(43)(44)(45) involving the concept of biological optimization. However, research in this area is still in the initial stage, and it will take a long way to replace physical optimization with biological optimization.…”
Section: Discussionmentioning
confidence: 99%